Interferon-lambda 3 and 4 Polymorphisms Increase Sustained Virological Responses and Regulate Innate Immunity in Antiviral Therapy With Pegylated Interferon-Alpha - Silva, Andréa Marques Vieira da; Alvarado-Arnez, Lucia Elena; Azamor, Tamiris; Batista-Silva, Leonardo Ribeiro; Leal-Calvo, Thyago; Bezerra, Ohanna Cavalcanti de Lima; Ribeiro-Alves, Marcelo; Kehdy, Fernanda de Souza Gomes; Neves, Patrícia Cristina da Costa; Bayma, Camilla; Silva, Jane da; Souza, Alessandro Fonseca de; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Sustained virologic response (SVR) in chronic hepatitis C (CHC) treatment denotes that the host genetics controls the immune response and unequivocally contribute to viral clearance or disease severity. In this context, single nucleotide polymorphisms (SNPs) in the locus of interferon lambda 3 and 4 genes (IFNL3/4) have been important genetic markers of responsiveness to CHC as prognostic markers for the pegylated-Interferon-alpha/ribavirin (Peg-IFN-α/RBV). Here, we analyzed 12 SNPs at the IFNL3/4 region in 740 treatment-naïve patients with CHC infected with hepatitis C virus (HCV) genotypes 1, 2, or 3 treated with Peg-IFN-α/RBV. Individually, rs12979860-CC, rs8109886-CC, or rs8099917-TT were predictive markers of SVR, while rs12979860-CC demonstrated the stronger effect. Besides, the genotypic combination of these three predictors’ genotypes, CC/CC/TT, increased the rate of SVR. Serum levels of cytokines and gene expression analysis on the genes IFNL3, IFNL4, IFNA1, and some of the IFN-stimulated genes (ISGs) were measured in a subgroup of 24 treated patients and 24 healthy volunteers. An antagonist effect was highlighted between the expression of IFNL3/4 and IFNA1 mRNA among patients. Besides, a prominent production of the pro-inflammatory chemokines CCL4 and CXCL10 was observed at a 12-week treatment follow-up. Lower serum levels of these chemokines were detected in patients with an rs12979860-CC genotype associated with the better treatment outcome. Also, lower expression levels of the IFI6, IFI16, IRF9 genes were observed among rs12979860-CC individuals. In conclusion, a combination of the genotypes at the IFNL3/4 locus can act as a better marker for the prognosis for virological responses in an admixed Brazilian population presenting the modulating effect over innate immunity and inflammation that are controlling the outcome of the viral infection, but also other infectious diseases. This study is registered on the ClinicalTrials.gov platform (accession number NCT01889849 and NCT01623336).